The epistemic change in geographic explanation and its pedagogical contributions in school geography - Rivera, José Armando Santiago (Revista Ensino de Geografia (Recife), 2023)
The purpose of the article is to reflect on the pedagogical effect of the application of the fundamentals of the qualitative approach to science in the innovation of school geography. It is assumed that in the contemporary world, as a consequence of the epistemic change, geography teaching has the opportunity to give a renewed formative treatment in the pedagogical and didactic aspects, to the understanding of the complex geographic reality, from the foundations of qualitative epistemology. In fact, methodologically, the epistemological change and the qualitative approach to science are analyzed in order to explain the pedagogical influence of the qualitative approach in school geography. It concludes by highlighting the importance of the experience acquired by citizens in their communal performance, in social initiatives to address the difficulties affecting communities. It is a renewed contribution whose aim is to provide knowledge and accurate, timely and relevant practices in the effort to modernize the teaching of geography, in accordance with the critical explanation of the complex reality of the contemporary world.